2003
DOI: 10.1021/ja037665w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (3S,5R)-Carbapenam-3-carboxylic Acid and Its Role in Carbapenem Biosynthesis and the Stereoinversion Problem

Abstract: (5R)-Carbapenem-3-carboxylic acid is the simplest structurally among the naturally occurring carbapenem beta-lactam antibiotics. It is the produced from (3S,5S)-carbapenam-3-carboxylic acid utilizing a remarkable stereoinversion/desaturation process by CarC (carbapenem synthase), an alpha-ketoglutarate dependent non-heme iron oxygenase. In this communication, we demonstrate for the first time that the epimeric (3S,5R)-carbapenam-3-carboxylic acid is an intermediate in the overall catalytic cycle to the carbape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…The (3S,5S)-carbapenam (2) was synthesized as described previously (32). Compounds 8,9,13,14,16 (33), 10-12 (34, 35), and 15 (36, 37) were derived from previous synthetic strategies as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The (3S,5S)-carbapenam (2) was synthesized as described previously (32). Compounds 8,9,13,14,16 (33), 10-12 (34, 35), and 15 (36, 37) were derived from previous synthetic strategies as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…1D, left) in addition to the desaturation reaction discussed above (20). Epimerization, unusual among the Fe(II)/2OG oxygenases, is redox-neutral (75), and this unprecedented reactivity has led to intensive studies to investigate the mechanism. For example, the crystal structure of CarC in complex with the substrate analogue (S)-N-acetylproline along with analyses from computational studies led to several possible mechanisms for the epimerization of the C5 position involving a C5-radical intermediate and an external H-atom donor (30,73,76).…”
Section: Epimerizationmentioning
confidence: 99%
“…1 Apart from the carbapenem product, the CarC catalytic reaction usually yields some amount of the saturated (3S,5R)-carbapenam, which differs from the substrate only in its configuration at the C5 carbon. [1][2][3] Because this saturated product can also be a substrate for CarC, it has been proposed that it can be, but is not necessarily, an intermediate in the overall conversion of (3S,5S)-carbapenam to (5R)-carbapenem. 2,3 A mechanistically important observation has been made in the isotopic labeling studies, which indicates that the bridgehead hydrogen (bound to C5) is lost in the CarC-catalyzed reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Because this saturated product can also be a substrate for CarC, it has been proposed that it can be, but is not necessarily, an intermediate in the overall conversion of (3S,5S)-carbapenam to (5R)-carbapenem. 2,3 A mechanistically important observation has been made in the isotopic labeling studies, which indicates that the bridgehead hydrogen (bound to C5) is lost in the CarC-catalyzed reaction. 2,4 It has been shown that the (3R,5R)-carbapenam is also processed by CarC, and that, when using purified enzyme, ascorbate stimulates turnover of the substrates requiring epimerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation